Analisis Porositas Batugamping Sebagai Reservoir Air Tanah Daerah Bintalahe, Kabupaten Bone Bolango, Provinsi Gorontalo - Hisyam, Febrina; Permana, Aang Panji; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2024)
Reservoir rocks are subsurface rocks that are porous and able to store and flow groundwater that can be utilized by the surrounding community. The rocks that function as groundwater reservoirs in the Bintalahe area are limestone. Almost the entire research area is composed of limestone so it is interesting to study. Gorontalo is located on the northern arm of Sulawesi which is bordered by two provinces and two seas, namely North Sulawesi Province in the east, Central Sulawesi Province in the west, Tomini Bay in the south and the Sulawesi Sea in the north. Gorontalo has interesting geological diversity to study, especially in Bintalahe Village. This study aims to analyze the porosity value of each limestone facies in the research area. The methods used are field observation and laboratory analysis as well as analysis of the specific gravity of coarse aggregate. The results of the study consist of three limestone facies, namely mudstone facies, batupakes facies and pumice facies. The potential of limestone in the Bintalahe area as a groundwater reservoir is in the category of poor to quite good.